Alpine ski edge sharpness and slicing - Flegel, D.; Kern, R. J.; Guo, S.; Brown, C. A. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Techniques are proposed here to understand how ski edge sharpening improves performance and increases risks of disfiguring and life-threatening lacerations (Holden et al. 2022). Previous models for edge snow interactions were from machining by chip formation for movement perpendicular to an edge (Brown 2009), essentially sideslipping. In contrast, slicing is studied for movement parallel to an edge, essentially carving. Skidded turns can have both. Slicing mechanisms have been studied, and edges characterized for teeth (Frazzetta 1988), knives (McGorry 2005), and stone tools (Stemp et al. 2019), although these are essentially blades having narrow solid angles. Edge sharpness has been characterized traditionally by their solid angles and estimating edge radii, e.g., Denkena (2011) for metal cutting tools with large solid angles, similar to ski edges.